National and international R&D support programmes and technology scouting in European small and medium enterprises (SMEs) - Dragana Radicic (University of Lincoln, Lincoln International Business School, Lincoln Economics and Finance Research Group (LEAF), 2019)
This paper evaluates the effectiveness of national and international R&D support programmes on firms' technology scouting, defined as firms' use of external knowledge sources. Drawing on a unique dataset on R&D support programmes for small and medium-sized enterprises (SMEs) operating in both manufacturing and service sectors across 28 European countries, this study reports treatment effects estimated by the copula-based endogenous switching model, which takes into account unobserved firm heterogeneity. Empirical results indicate that R&D support programmes have heterogenous effects on technology scouting, whereby a crowding out effect arises in the case of a short-run scouting, while additional effect are mostly reported for strategic external knowledge sourcing. Moreover, our results suggest that unfavourable, crowding out, effects could be reduced, if not eliminated, by a random distribution of public funding.
Keywords: 330; Technology scouting; External knowledge search; European SMEs; copula-based endogenous switching model